WILLIAMSON AND THE “JUDGMENT SKEPTIC” - Borges, Rodrigo (Intuitio, 2008)
ABSTRACT: In his latest book, Timothy Williamson (‘The Philosophy of Philosophy’) discusses the role of intuitions in philosophical methodology. In this paper I reconstruct Williamson’s discussion and criticize his take on the subject. My criticism is twofold: first, contrary to what Williamson suggests, some version of the philosophical conception which underlies the way philosophers usually think about intuitions must be right and, secondly, the alternative approach to intuitions offered by Williamson is mistaken. Key Words: Intuition. Knowledge. Skepticism. Belief. Judgments. ** WILLIAMSON E O “JUÍZO CÉTICO” RESUMO: Em seu livro mais recente, Timothy Williamson (‘The Philosophy of Philosophy’) discute o papel da intuição na metodologia filosófica. Neste artigo eu reconstruo a discussão de Williamson e critico a sua maneira de tratar do assunto. A minha crítica tem duas partes: primeiro, contrário ao que Williamson sugere, alguma versão da concepção filosófica que tem por base a maneira com que filósofos usualmente pensam intuição deve estar certa e, em segundo lugar, a teoria alternativa sobre intuição oferecida por Williamson está errada. Palavras-chave: Intuição. Conhecimento. Ceticismo. Crença. Juízos.